ANALISIS ALIRAN DAYA PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) ON – GRID 3540 Wp MENGGUNAKAN KWH METER DUA ARAH PADA LABORATORIUM TEKNIK MESIN, FAKULTAS TEKNIK UKI – JAKARTA DENGAN BEBAN MESIN PENCACAH SAMPAH 2 HP - Menara Immanuel Situmorang; Nempung, Judo Ignatius; Soebagio, Atmonobudi; Silalahi, Eva Magdalena (Prodi Teknik Elektro FT UKI, 2024)
The PLTS installed at the Mechanical Engineering Laboratory, Faculty of Engineering, UKI Jakarta is an On-Grid PLTS that plays a significant role in the development of technology and research in the fields of mechanical engineering and energy. The 2 HP waste shredder, used to recycle waste into reusable materials, is part of the efforts towards sustainability and efficient waste management. To support the operation of the waste shredder and reduce electricity costs, the laboratory has installed an On-Grid PLTS with a capacity of 3540 Wp. Based on power measurement data under no-load and load conditions with the 2 HP waste shredder, there was an energy export of 8 kWh and an energy import of 1 kWh over 11 hours. The power factor under no-load conditions was good, ranging from 0.96 to 1, which meets the standards set by PLN. However, the power factor when using the 2 HP waste shredder load ranged from 0.1 to 0.72, which does not meet PLN standards. The low power factor is due to the inductive load effect of the single-phase induction motor, such as that of the 2 HP waste shredder.